Case Report: Human Recombinant Growth Hormone Therapy in a DSH Cat Presented With Dwarfism - Načeradská, Martina; Návojová Horáčková, Kateřina; Fridrichová, Michaela (Frontiers in Veterinary Science, 2021)
A six-month-old kitten, male, domestic shorthair cat was presented with dwarfism, ocular and nasal discharge and Ascaris infestation. Congenital hyposomatotropism was diagnosed on the basis of serum level of Insulin-like growth factor-1 (IGF-1). The cat was treated with human recombinant growth hormone for 9 weeks, after that his liver enzymes became elevated and the therapy was discontinued. His IGF-1 levels were normal at the end of the therapy. Normal IGF-1 was present three month after discontinuation of therapy with human recombinant growth hormone as well as six months later and even half year after the discontinuation. All other comorbidities were addressed with the therapy. The cat is now the size of normal cats, living with the first author.